2017
DOI: 10.1038/s41598-017-07162-3
|View full text |Cite
|
Sign up to set email alerts
|

2-Dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione inhibits the growth and metastasis of breast carcinoma in mice

Abstract: Metastasis causes approximately 90% of breast cancer-related deaths in women. Previously, we have demonstrated that 2-dodecyl-6-methoxycyclohexa-2,5-diene- 1,4-dione (DMDD) remarkably inhibited the growth of human breast cancer cells with little toxicity. In this study, we investigated the toxicity and efficacy of DMDD to treat metastatic breast tumors using an in vivo mouse model of the 4T1 mammary carcinoma. DMDD caused no observable toxicity and significantly extended the survival of 4T1 tumor-bearing mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Therefore, the H&E staining images of representative sections of lungs are illustrated (Figure 5C). Typical tumor nodules were observed in the saline group, visualizing the metastasized cancer cells and their localization, as reported previously 35,36. Smaller and fewer nodules were found in lungs with IFN‐γ and NP‐TOS15 treatment, indicating the lung metastasis was inhibited to some degree.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, the H&E staining images of representative sections of lungs are illustrated (Figure 5C). Typical tumor nodules were observed in the saline group, visualizing the metastasized cancer cells and their localization, as reported previously 35,36. Smaller and fewer nodules were found in lungs with IFN‐γ and NP‐TOS15 treatment, indicating the lung metastasis was inhibited to some degree.…”
Section: Resultssupporting
confidence: 83%
“…Immunohistochemical procedures were conducted according to our previous study [ 52 ]. Briefly, the deparaffinized and hydrated slides were incubated in 3 % H 2 O 2 for 30 min to block the endogenous peroxidase activity and were later placed in citrate buffer (PH = 6) for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…This study uses a high-power infrared laser (at 1064 nm) to measure the radio sensitivity of 4T1 breast carcinoma cell lines treated by a naturally occurring compound, 2-Dodecyl-6-methoxycyclohexa-2, 5-diene-1, 4-dione (DMDD) extracted from the root of Averrhoa carambola L. Studies have shown that DMDD induces apoptosis of various human breast cancer cells through production of intracellular reactive oxygen species (ROS) and inhibition of NF-κB activation 21 . Recent studies, using an in vivo mouse model of transplanted 4T1 breast cancer cells, have also shown that DMDD effectively suppressed the growth of primary breast tumor and simultaneously inhibited the metastasis of breast tumor to the lung and liver, as well as prolonged the survival of tumor-bearing mice 22 . The 4T1 breast carcinoma cell line is highly tumorigenic and invasive; it can metastasize from the primary tumor to multiple distant sites such as lymph nodes, liver, lung, brain, and bone 22 .…”
Section: Introductionmentioning
confidence: 99%